The relationship between leadership and post traumatic growth following deployment related trauma in the New Zealand Defence Force : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatu, New Zealand. EMBARGOED until 13th November 2026 - Gibbs, Daina (Massey University, 2024)
Following a traumatic experience, there is the potential to benefit from posttraumatic growth (PTG). Research points to the ability of leadership to reduce negative consequences of trauma; consequently, recent investigations into PTG in military populations have theorised that positive leadership should enhance PTG outcomes for subordinates, though these hypotheses have yet to be tested. This study aimed to address this gap in the literature by investigating the relationship between leadership and PTG for those with and without potentially traumatic experiences (PTEs) in a sample of 445 previously deployed New Zealand Defence Force (NZDF) personnel. A quantitative, correlational study with longitudinal and cross-sectional designs was used to investigate the existence of a linear relationship between the concepts over time. Data was collected by the NZDF at two points in time, immediately following personnel’s return to New Zealand from an overseas deployment and then six months later. Access to demographic information, PTEs, leadership experiences, PTG, level of distress, and posttraumatic stress symptom data collected at both points in time was provided. A range of statistical analyses, including independent t-test, Kendall’s tau-b, and regression analyses, were employed through SPSS. The results showed that the rate and level of PTG were lower in those without PTEs, and there were no significant correlations or predictive ability found between leadership and PTG for those without PTEs. Contradicting expectations, only insignificant or weak negative correlations were found between PTG and leadership for those with PTEs, and leadership only showed a small amount of predictive utility. This may suggest that, when viewed in conjunction with preceding evidence, either; leadership does not have a direct relationship with PTG but may promote an environment in which PTG is more likely, or that positive leadership inhibits PTG as it protects a person from the negative effects of trauma, deterring the growth process. The inability to control several possible confounding variables likely impacted the validity of the results; consequently, more robust future research that can control a larger number of confounds and run more complex analyses is recommended.
Embargoed until 13th November 2026.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)